1996
DOI: 10.1046/j.1365-2133.1996.d01-1036.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum type III procollagen aminopeptide for assessing liver damage in methotrexate-treated psoriatic patients

Abstract: This study was designed to establish whether measurement of a serological marker of fibrosis might reduce the need for liver biopsy in psoriatic patients receiving methotrexate (MTX). Levels of type III procollagen aminopeptide (PIIINP-O and PIIINP-B) and laminin P1 (LamP1-B) were measured in 147 serum samples taken at the time of liver biopsy in 87 patients receiving long-term MTX treatment for severe psoriasis. Biopsies were classified as: (1) normal, (2) steatosis, (3) inflammation, (4) fibrosis, or (5) cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 21 publications
2
46
0
1
Order By: Relevance
“…Performing a liver biopsy only in patients with an abnormal PIIINP resulted, according to the study of Maurice et al [14], in a 45% reduction of all liver biopsies and the study of Chalmers et al [13 ]in a sevenfold reduction, without important liver damage being missed. Boffa et al [15 ]and Zachariae et al [8, 16, 17 ]also concluded that the chance to develop substantial liver fibrosis and the risks of missing significant liver damage are minimal in case of persisting normal PIIINP values.…”
Section: Discussionmentioning
confidence: 99%
“…Performing a liver biopsy only in patients with an abnormal PIIINP resulted, according to the study of Maurice et al [14], in a 45% reduction of all liver biopsies and the study of Chalmers et al [13 ]in a sevenfold reduction, without important liver damage being missed. Boffa et al [15 ]and Zachariae et al [8, 16, 17 ]also concluded that the chance to develop substantial liver fibrosis and the risks of missing significant liver damage are minimal in case of persisting normal PIIINP values.…”
Section: Discussionmentioning
confidence: 99%
“…In more recent years. PIIINP has been studied further in psoriatics on MTX [11][12][13], Also these studies indicated its value for measuring abnormal hepatic fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…En Europa, 20% de los dermatólogos lo usa rutinariamente para la detección de fibrosis hepática secundaria a metotrexato 9 , lo que lleva a que la monitorización con pruebas hepáticas se realice más espaciada, esto es cada 2 meses o más. Se recomienda controlar niveles de PIIIP cada 3 meses durante un tratamiento continuo de metotrexato 28,29 , con indicación de biopsia, sólo en caso de niveles persistentemente altos 21 . Esto ha logrado disminuir 7 veces la necesidad de biopsia hepática en paciente psoriáticos tratados con metotrexato, con un costo menor y la preferencia de los pacientes 26 .…”
Section: Conclusionesunclassified